Bridging the Wealth Gap - Mehta, MD, Roma (Clinical Medicine And Health Research Journal, 2024)
In this opinion piece supported by empirical studies, the author will argue the significance of educating women on financial literacy, asserting its pivotal role in enhancing outcomes for both physicians and the healthcare systems within which they operate. It is well-documented that financial strain correlates with burnout among physicians and trainees, resulting in substantial losses in productivity amounting to millions of dollars. It is postulated that fostering financial empowerment in women may serve as a strategic intervention to mitigate stressors and consequently ameliorate overall well-being within the medical institutions.